Tindakan Pidana atas Pelanggaran Hak Cipta pada Digitalisasi Ciptaan - Putu Lisa Putri Maharani (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2025)
The development of digitalization has brought significant progress in the dissemination and accessibility of creative works, particularly through digital platforms that enable rapid and widespread distribution. The digitalization of creative works provides significant opportunities for creators and the creative industry to expand market reach and increase creative productivity. However, on the other hand, this progress also poses various challenges, particularly related to the increase in copyright infringement such as piracy, unauthorized duplication, and illegal distribution of digital content. This article aims to examine criminal acts against copyright infringement in the digital era based on Law Number 28 of 2014 concerning Copyright. The research methods used are literature study and case analysis to identify types of digital copyright infringement, the application of criminal law, obstacles in law enforcement, and possible solutions. In addition, this article also analyzes the effectiveness of applicable legal regulations and the impact of copyright infringement on the sustainability of the creative industry. The results of the study indicate that firm and adaptive law enforcement to technological developments is crucial to protect creators' rights and maintain the sustainability of creativity in the digital era.